Liposomal Cosmeceuticals as Skin Protectives and Curatives - Barge, Kajal; Tank, Shivali; Parab, Bhagyashri; Nagarsenker, Mangal; Shidhaye, Supriya (Indian Journal of Pharmaceutical Education and Research, 2024)
Lifestyles and environmental changes draw people away from healthy and natural-looking skin. To hide the impaired and damaged skin texture as a result of several factors, people mostly prefer decorative cosmetics to get an immediate but temporary result. To overcome this problem, cosmeceuticals are emerged containing skin-protective and curative agents in a cosmetic base. The market is full of skincare products and many of them have proven unsatisfactory to the consumer. Liposome, a novel lipoidal carrier, overcome the limitations of conventional therapies. Liposomes are proven to deliver a wide variety of drug cargo to the targeted skin layer with negligible drug loss. This delivery platform got wide acceptability among users due to its remarkable efficacy and safety. Many more evolutions occurred in conventional liposomes over time and it is still an area of interest for researchers. To date, it has given outstanding performance in the broad areas of skincare and has grabbed the global skincare market in a short span of time. As this approach is evolving rapidly, developed countries have set their own separate protocols regarding nano-materials used in cosmetics. The present review focuses on newer liposomal cosmeceuticals and their actives as skin protectives and curatives.
Keywords: Cosmeceutical; Skin care; Skin protective; Curative; Liposomes